A Novel Multiuser Detector for LDPC-Coded DS-UWB Space Formation Flying. Issue 1 (March 2020) - Ma, Bo; Liu, Qingzhi; Wu, Zhilu; Jiang, Xu
Abstract: Space formation flying has attracted a lot of attention recently. In this paper, we using direct-sequence ultra-wideband (DS-UWB) as the physical layer of inter-spacecraft communications. The traditional multiuser detection method like soft-input soft-output (SISO) cost too much computation. The proposed multiuser detector no longer uses interleaving, and the computational complexity has a linear relationship with the number of users. The bit error ratio (BER) simulation result shows that the proposed method approaches the single-user system with increasing signal-to-noise ratios (SNRs).